Hematological Indices for Differential Diagnosis of Beta Thalassemia Trait and Iron Deficiency Anemia. (10th April 2014) - Vehapoglu, Aysel; Ozgurhan, Gamze; Demir, Ayşegul Dogan; Uzuner, Selcuk; Nursoy, Mustafa Atilla; Turkmen, Serdar; Kacan, Arzu
Abstract : Background . The two most frequent types of microcytic anemia are beta thalassemia trait ( β -TT) and iron deficiency anemia (IDA). We retrospectively evaluated the reliability of various indices for differential diagnosis of microcytosis and β -TT in the same patient groups. Methods . A total of 290 carefully selected children aged 1.1–16 years were evaluated. We calculated 12 discrimination indices in all patients with hemoglobin (Hb) values of 8.7–11.4 g/dL. None of the subjects had a combined case of IDA and β -TT. All children with IDA received oral iron for 16 weeks, and HbA2 screening was performed after iron therapy. The patient groups were evaluated according to red blood cell (RBC) count; red blood distribution width index; the Mentzer, Shine and Lal, England and Fraser, Srivastava and Bevington, Green and King, Ricerca, Sirdah, and Ehsani indices; mean density of hemoglobin/liter of blood; and mean cell density of hemoglobin. Results . The Mentzer index was the most reliable index, as it had the highest sensitivity (98.7%), specificity (82.3%), and Youden's index (81%) for detecting β -TT; this was followed by the Ehsani index (94.8%, 73.5%, and 68.3%, resp.) and RBC count (94.8%, 70.5%, and 65.3%). Conclusion . The Mentzer index provided the highest reliabilities for differentiating β -TT from IDA.